Valorization of chemically-treated recycled carbon black as a filler in biodegradable cellulose-based mulching films - Nur Alia Sahira Azmi,; Siew, Xian Chin; Sarani Zakaria,; Tian, Junfei; Chin, Hua Chia (Penerbit Universiti Kebangsaan Malaysia, 2025)
Researchers are exploring ways to incorporate carbon-based fillers like recycled carbon black (rCB) into cellulose films for use as biodegradable mulching films in agriculture. Adding dark fillers can increase opacity to control light exposure and moisture for optimizing crop environments. This study aimed to create an eco-friendly black mulching film by mixing treated rCB into a regenerated cellulose matrix derived from cotton linters. The rCB was chemically treated to modify its properties. Cellulose films were made with 10%, 25%, and 50% treated rCB mixed into a cotton linter cellulose solution. The films were characterized for properties like morphology, transparency, thermal stability, wettability, water vapor permeability, tensile strength, and soil biodegradation. Compared to untreated rCB, the treated filler improved the films’ cross-section, surface area, and porosity. Higher rCB increased opacity but decreased tensile strength. Adding 10% treated rCB optimized the decomposition rate. Increasing to 50% progressively slowed decomposition. The rCB made the films more hydrophilic, and 10% treated rCB gave the best water vapor transmission performance. While rCB did not impact overall biodegradability, the 10% treated rCB film degraded fastest in soil once surface deterioration began. In summary, incorporating 10% chemically treated recycled carbon black into cellulose films derived from cotton linters produced an optimized eco-friendly black biodegradable mulching film material.